2020
DOI: 10.1002/adfm.202002120
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Na–SO2Battery with Ethylenediamine Additive in Ether‐Based Electrolyte

Abstract: Rechargeable metal-SO 2 batteries have drawn tremendous attention because it can accelerate SO 2 fixation/utilization and offer high energy density. Herein, a rechargeable Na-SO 2 battery based on an ether-based liquid electrolyte with an ethylenediamine (EDA) additive is realized via the reversible formation/decomposition of Na 2 S 2 O 4 . Experimental investigations reveal that the EDA additive provides three benefits by simultaneously decreasing the overall electrode polarization, increasing the full discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Along the process of further expanding the above system, it is found that similar reaction between metallic Na and EDA cannot occur, which have been verified by both density functional theory (DFT) calculation (Figure 5(C)) and experiments. 67 Even though the EDA additive could effectively enhance the corrosion resistance of Na anode and reduce the overall electrode polarization, the cross-linking reaction of G4 solvent could not be performed, and thus no gel formed.…”
Section: Cross-linking Initiated By LI O Bondmentioning
confidence: 99%
“…Along the process of further expanding the above system, it is found that similar reaction between metallic Na and EDA cannot occur, which have been verified by both density functional theory (DFT) calculation (Figure 5(C)) and experiments. 67 Even though the EDA additive could effectively enhance the corrosion resistance of Na anode and reduce the overall electrode polarization, the cross-linking reaction of G4 solvent could not be performed, and thus no gel formed.…”
Section: Cross-linking Initiated By LI O Bondmentioning
confidence: 99%
“…Among metal-gas battery systems, [41][42][43][44] Li-CO 2 batteries have been well-placed to achieve energy storage and release because of the high theoretical energy density and CO 2 fixation/ utilization. [45,47] In such a system, the battery generally operates on the principle that Li 2 CO 3 and carbon are generated and then decomposed at the cathode side (4Li + 3CO 2 ⇌ 2Li 2 CO 3 + C).…”
Section: Full-cell Behavior With Co 2 -Regulated LI + -Pcementioning
confidence: 99%
“…Ethylenediamine additives have recently gained attention, especially in ether-based electrolytes. The specific amount of ethylenediamine addition forms a Na2S2O4 selfhealing SEI layer with high discharge capacity, reduced polarization, and negligible corrosion effects [380]. As discussed earlier, Rb + and Cs + have also been studied as good additives for carbon-based electrodes in addition to FEC.…”
Section: Binders and Additives For Electrolytementioning
confidence: 99%